Correlation between Completeness of Basic Immunization and Other Factors with the Incidence of Acute Respiratory Infection in Toddlers - Susanto, Aries; Tirtawidjaja, Irwandy; Widjaya, Ivan Riyanto; Damayanti, Katarina; Iwan, Meyselina (Universitas Kristen Krida Wacana, 2022)
Acute Respiratory Infection (ARI) is a common disease that occurs in children under five. Indeveloping countries, the probability of the disease within an age group of toddlers estimated 29%cases per child/year and in developed countries 5% cases per child / year. It shows that there are 156million new cases per year in the world in which 151 million cases (96.7%) occur in developingcountries. Episode cold on Toddlers in Indonesia estimated 2-3 times per year (Rudan et al BulletinWHO 2008). This study aims to determine the correlation between the comprehensiveness of basicimmunization and other factors in terms of ARI on toddler in Cipejeuh Wetan – Cirebon withinJanuary to October 2016. The factors that are examined include comprehensiveness of basicimmunization, exclusive breastfeeding, nutrition, smoking behavior in the home. The design study iscross-sectional. Sampling technique is cluster random sampling with the primary data source in 62children under five years using questionnaire. The analysis is Chi-square. The statistical test showeda significant correlation between ARI against nutrition (p=0.015), smoking behavior in the home(p=0.009).